Effect of Using Augmented Reality-Assisted Learning Media on Elementary School Students' Learning Motivation in Social Studies Learning - Muhammad Nasheh Ulwan; Wahyu Sopandi; Encep Supriatna (MANDAILING GLOBAL EDUKASIA, 2026)
Despite the rapid integration of immersive technologies in STEM disciplines, the pedagogical potential of Augmented Reality (AR) in primary humanities education, particularly social studies, remains significantly under-researched. Social studies concepts are frequently perceived by young learners as abstract and monotonous, leading to a critical decline in academic engagement. This study aims to address this gap by examining the empirical effect of AR-assisted learning media on the learning motivation of elementary school students during social studies instruction. Employing a quantitative approach with a quasi-experimental design, this research involved 76 third-grade students from SD Negeri Anyar 1, purposively divided into an experimental class (n = 38, utilizing AR-integrated media) and a control class (n = 38, utilizing conventional instructional methods). Data on student motivation were rigorously collected through structured observation techniques and analyzed using both descriptive statistics and inferential parametric tests, including independent and paired-sample t-tests. The findings demonstrated that the integration of AR-assisted learning media exerts a highly positive and statistically significant effect on students' learning motivation. Descriptive analysis indicated that the experimental group achieved an exceptional post-test motivation score (M = 89.46, falling into the very high category), whereas the control group remained substantially lower (M = 60.15, categorized as low). Inferential statistical testing confirmed this disparity to be highly significant (p < 0.001). These results suggest that AR effectively bridges the gap between abstract historical or geographical concepts and the cognitive processing of young learners by providing interactive, three-dimensional visualizations. Consequently, this study underscores that AR-assisted media serves as a powerful pedagogical intervention to overcome low student engagement, offering valuable insights for educators and curriculum designers aiming to modernize primary education.